The Role of Governance in Achieving the Integrity Performance of Libyan Commercial Banks. - حسين القماطي أحمد; مفتاح بوفرنة فاخر (Dirasat in Economics and Business, 2026)
The main goals of this thesis are to investigate the level of application of governance standards in their various dimensions in Libyan commercial banks and their impact on the banks safety. The study’s sample is consisted of commercial banks operating in Libya with headquarters in Benghazi. These banks are Al-Wahda Bank, The Bank of Commerce and Development, and The Mediterranean Bank (Al-Motawaset Bank). The questionnaire is also handed out to 82 people, consisting of chairs of administrative boards, chairmen and members of committees affiliated with boards of directors, and managers of executive departments. This study employed the qualitative analysis to determine the level of application of banking governance standards in their various dimensions, The study data was analyzed by using the Statistical Analysis Program for Social Sciences (SPSS). The standard deviations, the cronbach’s alpha, the kolmogorov- smirnov’s, the one-sample t-test, the arithmetic averages, were used in this study. The study is concluded that the levels of application of banking governance standards with their dimensions (Eligibility & Independence of the Board of Directors and Executive Management, Efficiency & Independence of the Committees Emanating from the Board of Directors, The Bank’s Disclosure & Transparency Policy, and The Bank’s Procedures on Ensuring the Rights of Shareholders & Dealers) were all high. The Eligibility & Independence of the board of directors and executive management were the most commonly used governance dimensions while the least implemented were the dimensions of the bank’s disclosure and transparency policy. The results also showed that there is a strong positive correlation between the application of banking governance standards in their various dimensions and the integrity of banking performance. The most influential dimensions were the bank’s procedures dimension on guaranteeing the rights of shareholders & dealers, followed by the efficiency & independence of the committees emanating from the Board of Directors, followed by the Eligibility & Independence of the Board of Directors and the Executive Management. However, there is no significant effect of the bank’s disclosure and transparency policy dimension on the integrity of banking performance.